Presidenta não chora: o melodrama como olhar interpretativo dos documentários sobre o impeachment de Dilma Rousseff - Cavalcanti, Jaques (Universidade Federal de São Carlos, 2024)
The study of melodrama, traditionally linked to literary and cinematic studies, is increasingly being applied in sociological analyses addressing cultural and historical phenomena. This dissertation examines how the concept of melodramatic imagination, proposed by authors like Peter Brooks and Thomas Elsaesser, transcends the boundaries of gender studies and provides a powerful lens for analyzing documentary narratives about the impeachment of Dilma Rousseff. By highlighting how different documentaries adopt melodramatic strategies to portray the impeachment, an ideological polarization is revealed in which political figures are depicted as heroes or villains, influencing public opinion. The research emphasizes that melodrama is not merely a stylistic tool, but a moral language that shapes and legitimizes ideological discourse, offering a deeper understanding of contemporary political dynamics and the strategies for constructing their meanings.
President doesn't cry: melodrama as an interpretative lens on the documentaries of Dilma Rousseff's impeachment
Keywords: Melodrama; Impeachment; Dilma Rousseff; Imaginação melodramática; Melodramatic imagination; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA